Strategies of Silencing - Virágos, Zsolt K. (Hungarian Journal of English and American Studies, 2020)
Book review: Maxwell, William J. F. B. Eyes: How J. Edgar Hoover’s Ghostreaders Framed African American Literature. Princeton: Princeton UP, 2015. xiv + 363. ISBN 9780691130200. Hb. 29.95.